2020
DOI: 10.1111/jcmm.15001
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA profiles based on direct S‐Poly(T)Plus assay for detection of coronary heart disease

Abstract: Coronary heart disease (CHD) is one of the leading causes of heart‐associated deaths worldwide. Conventional diagnostic techniques are ineffective and insufficient to diagnose CHD with higher accuracy. To use the circulating microRNAs (miRNAs) as non‐invasive, specific and sensitive biomarkers for diagnosing of CHD, 203 patients with CHD and 144 age‐matched controls (126 high‐risk controls and 18 healthy volunteers) were enrolled in this study. The direct S‐Poly(T)Plus method was used to identify novel miRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Mechanically, we found that SP1 could transcriptionally up-regulate hsa-miR-320a expression in endothelium cell [16]. Recently, Su et al profiled miRNAs in the plasma from 203 patients with CHD and 144 age-matched controls (126 high-risk controls and 18 healthy volunteers) and showed that miR-320e was increased in CHD patients [54]. Moreover, correlation analysis indicated that miR-320e could be a better biomarker for CHD diagnosis compared to most conventional clinical factors, such as apolipoprotein A (ApoA), apolipoprotein B (ApoB), and LPA [54].…”
Section: Mir-320 Is a Potential Biomarker For Atherosclerosismentioning
confidence: 70%
See 1 more Smart Citation
“…Mechanically, we found that SP1 could transcriptionally up-regulate hsa-miR-320a expression in endothelium cell [16]. Recently, Su et al profiled miRNAs in the plasma from 203 patients with CHD and 144 age-matched controls (126 high-risk controls and 18 healthy volunteers) and showed that miR-320e was increased in CHD patients [54]. Moreover, correlation analysis indicated that miR-320e could be a better biomarker for CHD diagnosis compared to most conventional clinical factors, such as apolipoprotein A (ApoA), apolipoprotein B (ApoB), and LPA [54].…”
Section: Mir-320 Is a Potential Biomarker For Atherosclerosismentioning
confidence: 70%
“…Recently, Su et al profiled miRNAs in the plasma from 203 patients with CHD and 144 age-matched controls (126 high-risk controls and 18 healthy volunteers) and showed that miR-320e was increased in CHD patients [54]. Moreover, correlation analysis indicated that miR-320e could be a better biomarker for CHD diagnosis compared to most conventional clinical factors, such as apolipoprotein A (ApoA), apolipoprotein B (ApoB), and LPA [54]. Meanwhile, Liu et al also performed miRNA microarray analysis in an OPG −/− mouse model to identify miRNAs involved in vascular calcification, a major characteristic of atherosclerosis [55].…”
Section: Mir-320 Is a Potential Biomarker For Atherosclerosismentioning
confidence: 99%
“…The data from this study were consistent with previous studies. For example, a significant increase in miR-361-5p expression was also found in CHD patients compared with that in highrisk controls [22]. Wang et al found that miR-361-5p was significantly increased in AMI disease patients compared to that in healthy volunteers [23].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these skeletal muscle-derived miRNAs have also been detected in the bloodstream [40,[183][184][185][186][187][188][189][190][191][192][193][194][195][196][197][198][199]. However, to date it is unknown whether their circulating levels are modulated during cancer cachexia in humans.…”
Section: Other Skeletal Mirnas Identified In Mouse Models Of Cancer Cachexiamentioning
confidence: 99%